Decision Support System For Selecting The Best Non PNS Using Fuzzy Analytical Hierarchy Process Method - Hashidiq, Agil Rasyid; Budiraharjo, Raden (Telematika, 2025)
The most important aspect of human resource management greatly impacts the success of the agency by selecting the best employees. The best employees are those who have certain skills that can contribute to the success of the agency. Non-Civil Servant Government Employees (PPNPN) are honorary personnel recognized by the Government and the State who are needed by agencies to assist a job in the unit in need. Problems occur when selecting employees with performance every month, namely the absence of a system that supports decisions to determine the selection of the best non-civil servants in Cipamokolan Bandung Village, so that the selection of the best employees is currently still done manually. Thus the selection of the best employees is not accurate and very subjective. The purpose of this research is to provide solutions to these problems by creating a decision-making system in selecting the best non-civil servants in Cipamokolan Bandung Village. The method used is by applying the Fuzzy Analytical Hierarchy Process method which can overcome uncertainty and inaccuracy in judgment. The research results obtained from the selection of non-civil servant government employees using the web-based Fuzzy Analytical Hierarchy Process method can create efficiency and effectiveness in selecting the best employees in Cipamokolan Bandung Village.